GFPR 2021 Report Overview - McDermott, John (2021)
John McDermott GLOBAL FOOD POLICY REPORT Netherlands Discussion of IFPRI’s 2021 Global Food Policy Report: Transforming Food Systems After COVID-19 Co-Organized by The Dutch Ministry of Foreign Affairs, IFPRI and Netherlands Food Partnership APR 15, 2021 - 08:00 AM TO 09:15 AM EDT